LABOUR MARKET DYNAMICS AND TOTAL REWARDS STRATEGIES IN COPING WITH ECONOMIC UNCERTAINTY IN 2026 - Hidayat Hidayat; Fefti Yulian Mela (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
This article analyses the dynamics of the Indonesian labour market in 2026, characterised by economic uncertainty, AI disruption and a demographic dividend, with an unemployment rate of 4.68% yet a 60% dominance of informal employment, and formulates an adaptive total rewards strategy as an organisational response through personalised compensation (a 5.8% pay rise), pay equity, and wellbeing programmes that boost retention by 20% in the VUCA era. Through a systematic literature review, the study reveals a shift from job creation to job upgrading, as well as a transformation of rewards from financial to holistic, data-AI-driven approaches, with practical implications for Indonesian HR practitioners in navigating talent shortages, rising benefit costs, and JKP-ALMP policies. Key contributions include a local-global integrative framework for talent retention and strategic recommendations: allocating 10–15% of the HR budget to reskilling, conducting annual pay equity audits, and fostering public-private collaboration to ensure inclusive growth and regional competitiveness amidst 5% economic stagnation.